Dental Image Processing for Human Identification - Trivedi, Deven N.; Shah, Nimit D.; Kothari, Ashish M.; Thanki, Rohit M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents an approach to postmortem human identification using dental image processing based on dental features and characteristics, and provides information on various identification systems based on dental features using image processing operations. The book also provides information on a novel human identification approach that uses Infinite Symmetric Exponential Filter (ISEF) based edge detection and contouring algorithms. Provides complete details on dental imaging; Discusses the important features of a human identification approach and presents a brief review on DICOM standard for dental imaging; Presents human identification approach based on dental features.
Introduction -- Issues in Human Identification -- Standards of Medical Images -- Technical Background -- Dental Feature Extraction and Matching for Human Identification -- Future Directions.
Keywords: Signal processing; Biomedical engineering; Biometric identification; Dentistry; Forensic sciences; Computer vision; Signal, Speech and Image Processing; Biomedical Engineering and Bioengineering; Biometrics; Dentistry; Forensic Science; Computer Vision